(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In this article, cars were theoretically examined and the numerical values of the parameters of the mathematical models of the processes of changes in the quality of cars were determined. Software has been developed for modeling the laws of changes in the quality of cars